2013
DOI: 10.1049/mnl.2013.0113
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical porous copper materials: fabrication and characterisation

Abstract: Hierarchical porous copper bulk can be fabricated through chemical dealloying of porous CuAl intermetallics under free corrosion conditions. The obtained precursor porous CuAl intermetallics and as-dealloyed hierarchical porous copper were characterised using X-ray diffraction, a field-emission scanning electron microscope and energy dispersive X-ray spectroscopy. It was found that the hierarchical porous copper can be easily prepared by this method. The dealloying solution will dramatically influence the morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It is reported that the Al 4 Cu 9 phase is less susceptible to an alkaline environment compared to an acid environment. 35 Thus it is reasonable to recognize that Al 4 Cu 9 would take up a higher proportion in the residue aer the depletion of Al and Al 2 Cu and can consequently be detected as shown in Fig. 5d.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is reported that the Al 4 Cu 9 phase is less susceptible to an alkaline environment compared to an acid environment. 35 Thus it is reasonable to recognize that Al 4 Cu 9 would take up a higher proportion in the residue aer the depletion of Al and Al 2 Cu and can consequently be detected as shown in Fig. 5d.…”
Section: Resultsmentioning
confidence: 91%
“…[28][29][30][31][32][33] However, compared with widely studied ribbons and lms, precursors prepared through a sintering method are still less studied. 34,35 In this work, Al x Cu (100Àx) (x ¼ 60, 67 and 85 at%) alloy precursors were prepared through cold-press sintering followed by dealloying in an alkali solution under free corrosion conditions. The effects of the sintering parameters on precursors (Al 67 Cu 33 ) and products are studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…For the dealloying experiments, electrolytes of 0.1 M for HCl and 1.3 M for NaOH were chosen to compare our results with those in the literature. 13,26,27 Apart from the comparability, the ionic strength of the solutions is strong enough to entirely dissolve the Zn from the alloyed film in a proper dealloying time.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the respective potential shift for hydrogen evolution at pH 1 and pH 14, the electrochemical Zn oxidation is thermodynamically favored in acidic environment than that in alkaline. For the dealloying experiments, electrolytes of 0.1 M for HCl and 1.3 M for NaOH were chosen to compare our results with those in the literature. ,, Apart from the comparability, the ionic strength of the solutions is strong enough to entirely dissolve the Zn from the alloyed film in a proper dealloying time.…”
Section: Resultsmentioning
confidence: 99%
“…Special physicochemical properties of materials are associated with their structural hierarchy, such as the super-hydrophobic nature of lotus leaves and structural color of butterfly wings ( Song et al., 2018 ; Yang et al., 2017 ). In recent years, great advances have been achieved in design, fabrication, and application of hierarchically structured materials ( Juarez et al., 2017 ; Kong et al., 2013 ; Nyce et al., 2007 ; Parlett et al., 2013 ; Qiu et al., 2015 ; Shi et al., 2017 ; Sun et al., 2016 ; Zhang et al., 2019 ). For example, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%